Delayed Reconstruction after Eyelid Tumor Excision - Haefliger, I. O.; Tschopp, M.; Piffaretti, J.-M.; Pimentel, A.-R. (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: The aim of this study is to report the feasibility of one to two weeks delayed reconstruction after eyelid tumor excision. Patients and Methods: A retrospective case-series study was designed. Fourteen consecutive outpatients referred to a tertiary referral eye center for eyelid tumor management were enrolled. The intervention imvolved eyelid tumor excision (with four millimeters surrounding clinically tumor-free tissue), compressive patching of the excised area until reconstruction (with or without a therapeutic contact lens), extensive histological work-up to assess histological tumor clearance, and reconstruction one week after excision (in a couple of patients after two weeks when further excision was necessary to achieve tumor clearance). Excision and closure were performed by a single external trained oculoplastic surgeon (IOH) with a day per week (Fridays) operating slot. As outcome we assessed whether such an approach has led before, during, or after eyelid reconstruction to unusual major adverse events (follow-up time: 18 – 36 months).Results: Delaying up to one week, in some cases even two weeks, reconstruction after eyelid tumor excision was not associated with any unusual major adverse events before, during, or after surgery.Conclusions: When necessary, after eyelid tumor excision, it is possible to delay for one week or even for two weeks reconstruction, apparently without experiencing major unusual adverse events.
Keywords: delayed closure; surgical excision; Mohs’ micrographic frozen sections; Mohs’ surgery